THE BEGINNINGS OF OCCUPATIONAL MEDICINE IN INTERWAR POLAND – AN INTRODUCTION TO RESEARCH - Bartosz PASTERSKI (Humanities and Social Sciences, 2023)
This article presents the circumstances of the birth of occupational medicine in the interwar period in Poland. The first regulations concerning preventive examinations of young employees were created on the basis of the Act of July 2, 1924, concerning the work of minors and women. This act imposed an obligation on business entities to carry out free medical examinations for minors as ordered by the labor inspector. The first examination of underage employees was carried out in 1926. However, compliance with the laws and orders of the labor inspectorate during the interwar period left much to be desired. There was a shortage of doctors in the labor inspectorate, and a shortage of specialized medics to carry out the examinations. Despite the difficulties, the period in question saw the successful introduction of compulsory medical examinations for young workers. In 1930, 16,121 underage employees were diagnosed in this way. The interwar years also saw the first initiatives resulting from an increased awareness of preventive care for adult workers.